Synthesizing intra-individual and social comparisons: how integrated comparative advantage shapes math attitudes and gender stereotypes - Ran Liu (International Journal of STEM Education)
Abstract Background Despite gender similarity in math performance, gender disparities persist in math-related attitudes and STEM aspirations among adolescents globally. To disentangle this puzzle, some studies adopt the dimensional comparison theory to investigate the role of intra-individual comparative advantage across academic subjects, while others focus on the role of social comparison and peer performance in shaping student outcomes. The internal/external (I/E) frame of reference model has acknowledged that both intra-individual and social comparison processes matter. However, most studies measure and investigate the two processes separately, neglecting a potentially integrated comparison process. This study extends these theoretical strands by proposing the Integrated Comparative Advantage (ICA) model, which reveals the effects of an integrated comparison process beyond the separate effects of internal and external comparisons. This study focuses on the Integrated Comparative Math Advantage (ICMA) as a specific application of ICA in math. Results Utilizing information on classroom assignment rules from the nationally representative China Education Panel Survey (CEPS) data, this study exploits the quasi-random variation in ICMA. Linear regression models with school-grade fixed effects are used to estimate the ICMA effects on student outcomes controlling for student performance, intra-individual math advantage, and classroom average performance. Results show that boys have a higher ICMA than girls despite having lower performance in all subjects. A higher ICMA could boost student math self-assessment and improve math performance 1 year later. ICMA also exhibits gendered effects: the positive ICMA effects on math self-assessment persist for girls but not boys 1 year later; conversely, ICMA is positively associated with STEM aspirations for boys but not girls. Moreover, girls with a higher ICMA are less likely to endorse or perceive gender-math stereotypes, while it is the opposite for boys. Conclusions The findings suggest that intra-individual and social comparisons can jointly shape student attitudes and outcomes in an integrated process beyond their separate effects. Educators should thus be aware of the potential consequences of ability grouping, classroom assignment, and talent programs. Proactive measures can be implemented to directly challenge and dismantle stereotypes associated with the integrated comparative processes.